2021
DOI: 10.1111/acel.13471
|View full text |Cite|
|
Sign up to set email alerts
|

REST/NRSF deficiency impairs autophagy and leads to cellular senescence in neurons

Abstract: During aging, brain performances decline. Cellular senescence is one of the aging drivers and a key feature of a variety of human age‐related disorders. The transcriptional repressor RE1‐silencing transcription factor (REST) has been associated with aging and higher risk of neurodegenerative disorders. However, how REST contributes to the senescence program and functional impairment remains largely unknown. Here, we report that REST is essential to prevent the senescence phenotype in primary mouse neurons. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
0
18
1
Order By: Relevance
“…These results suggested that the activation of mTOR and inhibition of autophagy play an important role in neurosenescence induced by HGP. We also found that unlike a recent study reporting that the NRSF/REST deficiency induces autophagy reduction and cellular senescence in neurons [ 40 ], the down-regulation of NRSF/REST decreased the level of mTOR phosphorylation and promoted autophagy in neurons under HGP treatment. These discrepancies are possibly due to the different senile status of neurons and different subcellular changes of NRSF/REST.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results suggested that the activation of mTOR and inhibition of autophagy play an important role in neurosenescence induced by HGP. We also found that unlike a recent study reporting that the NRSF/REST deficiency induces autophagy reduction and cellular senescence in neurons [ 40 ], the down-regulation of NRSF/REST decreased the level of mTOR phosphorylation and promoted autophagy in neurons under HGP treatment. These discrepancies are possibly due to the different senile status of neurons and different subcellular changes of NRSF/REST.…”
Section: Discussioncontrasting
confidence: 74%
“…These discrepancies are possibly due to the different senile status of neurons and different subcellular changes of NRSF/REST. In the present study, neuronal senescence was induced by the HGP treatment, while in Rocchi’s study [ 40 ], neurons were under normal culture condition. Meanwhile, as discussed above, the increased NRSF/REST positive fluorescent particles mainly localized in the nucleus of normal “aging” neurons after relatively long-term culture, whereas elevated in the cytoplasm with abnormal punctates in the HGP-treated senile neurons.…”
Section: Discussionmentioning
confidence: 53%
“…A real-time quantitative PCR analysis was performed using the PowerUp™ SYBR™ Green Master Mix (A25742, Applied Biosystems Japan Ltd., Tokyo, Japan) and automated sequence detection systems (StepOne, Applied Biosystems Japan Ltd.). Relative gene expression was measured by previously validated primers for TNFα [ 31 ], IL-1β [ 32 ], IL-4 [ 33 ], TGF-β1 [ 34 ], Lcn2 [ 35 ], CtsB [ 36 ], CREB [ 37 ], BDNF [ 38 ], REST [ 39 ], and iNOS [ 40 ] genes. The primer sequences are set out in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, neuronal senescence in AD models is relatively complicated, and there is a growing concern about cell senescence in brain post-mitotic cells. Many evidence demonstrated that terminally differentiated neurons show some phenotypes similar to senescence, such as cell cycle arrest, SA-β-gal activity, lipofuscin, DNA damage response, and activation of SASP both in vitro and in vivo (Wong et al, 2009;Geng et al, 2010;Jurk et al, 2012;Ota et al, 2012;Kang et al, 2015;Forero et al, 2016;Rocchi et al, 2021). Therefore, preventing neuronal cells from senescence might be beneficial in the prevention and treatment of age-related neurodegenerative disorders, such as AD.…”
Section: Introductionmentioning
confidence: 99%